2021
DOI: 10.1111/ijsa.12346
|View full text |Cite
|
Sign up to set email alerts
|

A review of online reactions to game‐based assessment mobile applications

Abstract: This paper takes an exploratory approach to analyze reactions to game-based assessments (GBAs) by examining users' reviews of GBA mobile applications. In this study, we explore 3146 user reviews and 1253 comments from 10 GBA applications found on the two most popular mobile application distribution platforms using a natural language processing tool. Findings suggest that candidates generally perceive GBAs as novel and have varying reactions to specific game, assessment, and application elements. As this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In fact, more than half of the empirical research on GRA deals with this issue. Thus, we can confirm that GRA promote positive reactions in the applicants (Georgiou, 2021;al-Qallawi and Raghavan, 2022;Georgiou and Lievens, 2022) and tend to be better valued than conventional selection methods (Collmus and Landers, 2019;Georgiou and Nikolaou, 2020;Landers et al, 2021;Harman and Brown, 2022;Hommel et al, 2022). It is noteworthy that this result seems consistent across the different types of GRA, as these investigations have been conducted with very diverse games, starting with traditional assessment and going on to include serious games.…”
Section: Applicant Reactionssupporting
confidence: 67%
See 2 more Smart Citations
“…In fact, more than half of the empirical research on GRA deals with this issue. Thus, we can confirm that GRA promote positive reactions in the applicants (Georgiou, 2021;al-Qallawi and Raghavan, 2022;Georgiou and Lievens, 2022) and tend to be better valued than conventional selection methods (Collmus and Landers, 2019;Georgiou and Nikolaou, 2020;Landers et al, 2021;Harman and Brown, 2022;Hommel et al, 2022). It is noteworthy that this result seems consistent across the different types of GRA, as these investigations have been conducted with very diverse games, starting with traditional assessment and going on to include serious games.…”
Section: Applicant Reactionssupporting
confidence: 67%
“…On the other hand, we must acknowledge that not all reactions are positive. Thus, al-Qallawi and Raghavan (2022) study the reactions generated by nine serious games published in mobile application stores (App Store and Google Play). Through a qualitative approach, using natural language processing, they identify a general tendency to value GRA positively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. For data collection, the Python libraries "google-play-scraper " (available at https://pypi.org/ project/google-play-scraper/ ) [8] and the "app-store-scraper " (available at https://pypi.org/ project/app-store-scraper/ ) [9] were used [10] . The reviews were merged into a unified dataset and exported as a single Excel file.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Additionally, Landers et al (2022) found that their GBA was perceived more positively in terms of procedural fairness, distributive fairness, job relatedness, and test propriety compared with a paper‐pencil test. Furthermore, al‐Qallawi and Raghavan (2022) examined user reviews and comments from 10 GBA applications on two mobile distribution platforms. Generally, they found many positive evaluations from applicants, who particularly perceived GBAs as innovative.…”
Section: Development Of a Gba To Measure Cognitive Abilitymentioning
confidence: 99%